2003
DOI: 10.1016/s0042-6822(03)00415-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of avian reovirus:

Abstract: Nucleotide sequences of the S-class genome segments of 17 field-isolates and vaccine strains of avian reovirus (ARV) isolated over a 23-year period from different hosts, pathotypes, and geographic locations were examined and analyzed to define phylogenetic profiles and evolutionary mechanism. The S1 genome segment showed noticeably higher divergence than the other S-class genes. The sigma C-encoding gene has evolved into six distinct lineages. In contrast, the other S-class genes showed less divergence than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…Despite the limited sequence information, the analyses provided evidence that accumulation of point mutations and reassortment among cognate genome segments could have played a key role in the origin and evolution of strain AVS-B. This is in agreement with previous studies conducted on a subset of ARV genes [15][16][17][18][19][20][21] and is consistent with evolutionary strategies of the majority of other virus species within the Reoviridae family.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the limited sequence information, the analyses provided evidence that accumulation of point mutations and reassortment among cognate genome segments could have played a key role in the origin and evolution of strain AVS-B. This is in agreement with previous studies conducted on a subset of ARV genes [15][16][17][18][19][20][21] and is consistent with evolutionary strategies of the majority of other virus species within the Reoviridae family.…”
Section: Discussionsupporting
confidence: 87%
“…The availability of sequence information published over the past decade allowed analyses of the overall genetic architecture of ARV strains, molecular evolutionary and epidemiologic studies to be performed, and sensitive and specific molecular detection methods to be designed [15][16][17][18][19][20][21][22][23][24][25][26]. To the best of our knowledge, this study is the first to report the whole genome sequence of a wild type chicken ARV associated with a disease condition other than tenosynovitis.…”
Section: Discussionmentioning
confidence: 99%
“…This result agreed with previous serological data that the DRV was antigenically different to chicken reovirus S1133 [10,18]. Comparison of the S14 rC protein sequence with the r1 sequence of the mammalian reovirus strains revealed 14-16% identity, which was of the same order of magnitude as that between ARV and MRV [19,22]. Amino acid sequences and secondary structure prediction analysis showed the shorter size of DRV rC had a heptapeptide repeat and leucine zipper patterns in the Nterminal region which agreed with the recent investigations to ARV [13,[21][22][23] and MRV [24], concluded that DRV rC protein is functionally and structurally related to chicken and MRV homologous protein.…”
Section: Discussionsupporting
confidence: 91%
“…Comparison of the S14 rC protein sequence with the r1 sequence of the mammalian reovirus strains revealed 14-16% identity, which was of the same order of magnitude as that between ARV and MRV [19,22]. Amino acid sequences and secondary structure prediction analysis showed the shorter size of DRV rC had a heptapeptide repeat and leucine zipper patterns in the Nterminal region which agreed with the recent investigations to ARV [13,[21][22][23] and MRV [24], concluded that DRV rC protein is functionally and structurally related to chicken and MRV homologous protein. rC-encoding gene, by virtue of its type-specific epitopes [14,24,27], might have been subjected to an initial increased rate of evolution under strong immunological selection.…”
Section: Discussionmentioning
confidence: 99%
“…For the past several years, our laboratory has been studying molecular evolution of ARV and signaling pathways triggered by ARV required for apoptosis induction, virus replication, and cell cycle perturbations (22,(27)(28)(29)(30)(31)(32)(33). To date, the molecular events leading to endocytosis by ARV are still completely unknown.…”
mentioning
confidence: 99%